Design Engineering, Synthesis Protocols, and Energy Applications of MOF-Derived Electrocatalysts - Radwan, Amr; Jin, Huihui; He, Daping; Mu, Shichun (Nano-Micro Letters, 2021)
The core reactions for fuel cells, rechargeable metal–air batteries, and hydrogen fuel production are the oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER), which are heavily dependent on the efficiency of electrocatalysts. Enormous attempts have previously been devoted in non-noble electrocatalysts born out of metal–organic frameworks (MOFs) for ORR, OER, and HER applications, due to the following advantageous reasons: (i) The significant porosity eases the electrolyte diffusion; (ii) the supreme catalyst–electrolyte contact area enhances the diffusion efficiency; and (iii) the electronic conductivity can be extensively increased owing to the unique construction block subunits for MOFs-derived electrocatalysis. Herein, the recent progress of MOFs-derived electrocatalysts including synthesis protocols, design engineering, DFT calculations roles, and energy applications is discussed and reviewed. It can be concluded that the elevated ORR, OER, and HER performances are attributed to an advantageously well-designed high-porosity structure, significant surface area, and plentiful active centers. Furthermore, the perspectives of MOF-derived electrocatalysts for the ORR, OER, and HER are presented. Highlights: 1 Synthesis protocols, design engineering, theoretical calculations, and energy applications for metal–organic frameworks (MOFs)-derived electrocatalysts are systematically analyzed. 2 Synthesizing methods of MOF-derived catalysts and their oxygen reduction reaction, oxygen evolution reaction, and hydrogen evolution reaction electrocatalysis are discussed. 3 The current status, ongoing challenges, and potential future outlooks of MOFs-derived electrocatalysts are highlighted.